Ball-milling Process for the Synthesis of Pharmacological Tetrahydroquinoline Molecules through Multicomponent Povarov Reaction§ - Kouznetsov , Vladimir V.; Vargas-Méndez , Leonor Y. (Progress in Chemical Science Research Vol. 6, 2023)
Being key structural unit for numerous natural products and privileged scaffolds in medicinal chemistry, functionalized tetrahydroquinoline molecules display a wide spectrum of potent, interesting pharmacological activities, and unique physicochemical properties. Due to their significant biological activities and specific properties, new methods for obtaining functionalized tetrahydroquinoline (THQ) derivatives under green reaction conditions have attracted increasing attention in recent years. Among these, the three-component Povarov reaction is one of the most important synthetic strategies used for the generation of new potential bioactive quinoline derivatives. In this chapter, we discuss the chemistry and biology of some functionalized quinoline molecules that have been prepared through the Povarov reactions using mechanochemical activation. Pointing to a better understanding of the physicochemical properties of the obtained functionalized tetrahydroquinoline molecules, namely cis-4-amidyl-2-methyl-6-substituted THQs, for designing novel bioactive chemical entities, in-silico studies have been performed trying to find some structural-potential activities relationships based on Lipinski’s parameters. This chapter contains two general parts: synthetic aspects of the mechano-activated three-component Povarov reaction and known pharmacological properties of 4-amidyl-2-methyl-6-substituted THQs.